Optimalisasi Potensi Lele Melalui Sosialisasi Pembuatan Abon di Desa Gajahan, Kecamatan Colomadu, Kabupaten Karanganyar: Membangun Kemandirian Ekonomi Lokal - Setiawati, Desy; Rizky, Achmad Wahyu Nur; Isnaini, Indira; Sudarmono, Kevin Alexander Josa; Afifah, Mela Nur; Kurniawan, Riza; Rakasiwi, Septiana Gili; Monicadewi, Tessa; Salamah, Tiara Insan; Dewi, Tyas Kusuma; Asturanura, Vanissa Rezita (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
This study aims to optimize the potential of catfish cultivation through training activities for making catfish floss. So that it can increase the economic value of the harvest while reducing the risk of post-harvest decay when catfish production exceeds capacity. This study uses implementation methods that include: Identification and analysis of needs, licensing, program preparation, and implementation. The results of this study indicate an increase in community knowledge and skills on how to process catfish into floss, up to the packaging process. The conclusion in this study is that making catfish floss can be an effective solution in utilizing existing potential, and can improve the economy in the village.